Impacts of gestational depression on fetal development: an integrative review (Research, Society and Development, 2023)
During pregnancy, several physiological and psychological changes can occur in the pregnant woman's body, including the development or worsening of psychiatric pathologies, such as depression, which are influenced by the various hormonal, social and behavioral changes of women during this period. Objective: This work aims to evaluate the consequences of gestational depression on fetal development. Methodology: This integrative literature review was carried out by searching the SciELO, PubMed and BVS databases using the following Boolean descriptors and operators: antepartum depression OR gestational depression AND fetal development NOT postpartum. Results: The vast majority showed positive results of the influence of maternal depression on fetal development, with only three articles not finding evident relations. There are associations between gestational depression and fetal brain development, alterations in genetic expressions and unfavorable outcomes, including premature birth, shorter length and weight at birth and decreased head circumference. Of the thirteen articles included, all are analytical observational, twelve are cohort and one case-control. Conclusion: Despite the positive results, it is essential to have a methodological standard for research on the subject, in order to eliminate doubts generated by contradictory articles on specific points. In addition, taking into account other factors, such as social and economic, so that there are reliable results to reinforce the importance of care involving the mental health of pregnant women.